Tunable characteristics of porous silicon optical microcavities by energetic N ion beam interactions. (6th October 2021) - Verma, Chandra Prakash; Adnan, Mohammad; Srivastava, P; Asokan, K; Kanjilal, D; Vijaya Prakash, G
Abstract: The present study demonstrates the tuning of optical characteristics of porous silicon (PSi)-based microcavities by N ion beam interactions. These optical microcavities are prepared by using electrochemical etching of heavily doped p + -type Si. The PSi microcavities were exposed to N ions of 200 keV and 1 MeV at an optimized ion fluence of 1 × 10 15 ions cm −2 . A significant red-shifting of 32 ∼ 60 nm in the resonance cavity mode was observed due to ion interaction. The experimental results are in good agreement with the transfer matrix simulations. A substantial modification of the PSi microcavity surface states is visualized through Raman and x-ray photoelectron spectroscopy (XPS) techniques. The Raman spectral results show modifications from crystalline Si to nanostructured Si and subsequently to amorphous Si. The XPS indicates the modification of Si–Si and Si–O bonds and the formation of new Si–N bonds, implying the presence of Si3 N4 . These experimental observations, along with analytical simulations and transfer-matrix method microcavity modeling, conclusively support the realization of cavity tunability and substantial modification in the optical field intensity and photon confinement within the spacer layer of the microcavity. These results suggest that ion beams are the effective tool to produce wider tunable optical properties in microcavities with highly stable designer optical structures suitable for photonic applications.